Fungsi Hutan Menurut Persepsi Masyarakat di Desa Sekitar KPH Banyuwangi Selatan Perum Perhutani Divisi Regional Jawa Timur - Omo Rusdiana; Amelia Wardiman (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2020)
The issue of water scarcity is problem rife in various areas, especially in East Java. The aim of this study is to examine the causes of water scarcityin the village around the area Perum Perhutani South Banyuwangi KPH, Regional Division of East Java. In this study a head of village was appointment as key informance in villages were sampled to be interviewed.There are 30 respondents which represent each villages. Data were obtained from the representative with questionnaries, then analyzed descriptively. Based on the public preception of water scarcity during the dry season in Karangdoro and Sumbermulyo village is a slight different. Most of the villagers in Karangdoro didn’t experience the presence of drought due to availability of DAM and water at the well to the needs of household, while Sumbermulyo villagers suffered of drought due to lack of DAM, and unavailable water wells in the dry seasons. The majority of villagers of Karangdoro and Sumbermulyo agreed that the forest serves as the optimal land cover for catchments water, the aesthetics of nature, and nature conservation. Key words: forest function, perhutani, society perception, water, water scarcity